Configurações de educação a distância: um estudo sobre os marcos e fatores - Pereira, Heliese Fabrícia (2015)
Distance education has experienced a huge grown in recent years, either by technological advance, either by an idealized form of education access democratization. In spite of the substantial growth, there are many issues regarding the teaching-learning process by distance education. The main objective of this work is to make a literature review of key points that should be addressed for the educational concepts in the distance distance education process. In order to achieve this goal, it became necessary to establish specific objectives to answer questions which orientate the work development, namely: a) the legal basis of distance education in Brazil; b) the terminology and theoretical framework aspects of distance education; c) the analyzes of the aspects that define a distance education model. To meet these objectives, this work consists of an introduction, two chapters and the final remarks. In chapter 2, for the revision of concepts in distance education were taken in addition to the current legislation, studies of Belloni (2001, 2002); Bévort and Belloni (2009); Maia and Mattar (2007); Rosini (2007); Oliveira (2014); Saviani (2007); Moran (2002); Moore and Kearsley (2007) and Preti (2002). In Chapter 3, we carry out a literature review about the aspects that define a distance education model. The aspects taken in account were those considered the most relevant and which constitute the forefront of DE thinking. They were policies, guidelines, parameters and quality standards defined for each educational level and the specific course. Thus we discussed information and communication technologies; autonomy and interaction; teacher and tutor and teaching and learning. In the final remarks, we synthesized the analyses performed during this study.